Enhancement of Shelf-Life of Tomatoes Using Herbal Extracts - Kumar, R. Lakshmipathy, C. Surekha, K.V. Chethan (Journal of Phytology, 2009)
A study was taken up to enhance the shelf life of tomatoes by using Garlic (Allium sativam Linn) and Ginger (Zingiber officinale Rose) extracts at different concentrations viz, 1%, 5% and 10%. Tomatoes keeping quality was improved by spraying 10% garlic and ginger extracts, which reduced the spoilage, physiological loss and microbial load on the surface of the fruits. Among these, 10% garlic extract was more efficient in controlling spoilage microorganisms, enhancing shelf life and redicing physiological weight loss.Ã‚Â Ã‚Â This study revealed the possibility of utilization of Garlic (Allium sativam Linn) and Ginger (Zingiber officinale Rose) extracts to enhance the keeping quality of tomatoes.